Perspective of Law No. 40 of 2014 Concerning Sharia Life Insurance Business in Risk Management - Parmujianto Parmujianto (Maliki Islamic Economics Journal, 2021)
Sharia life insurance is a coverage or agreement between two parties in which one party is obliged to pay contributions or premiums. In sharia insurance, it is usually a contract in the form of a tijarah agreement and or tabarru contract. Where Tijarah contract is all forms of contracts carried out for commercial purposes such as Mudhorobah, Wadiah, and Wakalah. While Tabarru agreement is all forms of contracts that are done with the purpose of kindness and help is not shown for commercial. The approach used in this study is a qualitative approach. The conclusion in this discussion is that PT. Asuransi Syariah Keluarga Indonesia (ASYKI) Pasuruan Unit is good and in accordance with Law No.40 of 2014 concerning sharia life insurance business in risk management based on sharia principles, although it does not cover the possibility of individuals registering individually, but the recommended solution from PT ASYKI Pasuruan Unit against individual policy insurance applicants will be directed against one of business entity in cooperation with PT ASYKI Pasuruan Unit.